Short-term mobility in higher education: The case of the Manuel Andrés Sánchez Grants from the University of Salamanca - Gonzalo, Paula; Escamilla, Alonso (Journal of International Students, 2025)
Since the Bologna Declaration and the establishment of the European Higher Education Area (EHEA), international mobility has become a strategic pillar of universities in recent decades. In this context, the focus in both practice and academia has been mainly on long-term mobility. For this reason, the present research focuses on analyzing whether the Manuel Andrés Sánchez Grants (MAS Grants) of the University of Salamanca are a model of success in the implementation of short-term mobility programs within the EHEA, especially in cultural exchange and the development of both technical and soft skills among beneficiary students at the international level. A qualitative methodological approach based on in-depth interviews with the University of Salamanca, NGOs on the ground, and beneficiary students is applied. MAS Grants are a unique initiative in Spain that can be considered a good practice in the field of short-term mobility programs within the EHEA